Circularly Polarized Dielectric Resonator Antenna Arrays with Fractal Cross-Slot-Coupled DRA Elements - Jia-Hong Lin; Wen-Hui Shen; Zhi-Dong Shi; Shun-Shi Zhong (International Journal of Antennas and Propagation)
In the design of circularly polarized (CP) dielectric resonator antenna (DRA) arrays, the regular-shaped DRAs with simple feeding configurations are mostly used as array elements to make the design procedure more efficient. However, such array element DRA usually achieves only about 6% axial ratio (AR) bandwidth. In this paper, a CP DRA element coupled by a fractal cross-slot which can radiate efficiently and excite the rectangular DRA simultaneously is considered. By adjusting the dimensions of the fractal cross-slot properly, the resonances of the fractal cross-slot and the dielectric resonator can be merged to obtain a wider AR bandwidth. Based on the proposed fractal cross-slot-coupled CP DRA element, two different CP DRA arrays are designed: a wideband CP DRA array and a low-sidelobe-level (SLL) CP DRA array. The designed DRA arrays are fabricated and measured, and structures and performances of the arrays are presented and discussed.